MicroRNAs in Alzheimer’s Disease: Function and Potential Applications as Diagnostic Biomarkers - Wei, Wei; Wang, Zhi-Yong; Ma, Li-Na; Zhang, Ting-Ting; Cao, Yu; Li, Hao (Frontiers in Molecular Neuroscience, 2020)
Alzheimer’s disease (AD) is the most common form of dementia. Although the incidence of AD is high, the rates of diagnosis and treatment are relatively low. Moreover, effective means for the diagnosis and treatment of AD are still lacking. MicroRNAs (miRNAs, miRs) are noncoding RNAs that play regulatory roles by targeting mRNAs. The expression of miRNAs is conserved, temporal, and tissue-specific. Impairment of microRNA function is closely related to AD pathogenesis, including the beta-amyloid and tau hallmarks of AD, and there is evidence that the expression of some microRNAs differs significantly between healthy people and AD patients. These properties of miRNAs endow them with potential diagnostic and therapeutic value in the treatment of this debilitating disease. This review provides comprehensive information about the regulatory fuction of miRNAs in AD, as well as potential applications as diagnostic biomarkers.